
How do you solve -(1+7x)-6(-7-x)=36? - Socratic
2018年5月22日 · x=5 First I would multiply both sides with -1: -(1+7x)-6(-7-x)=36 =>1+7x+6(-7-x)=-36 =>1+7x-42-6x=-36 (Multiply 6 with each term in the parenthesis. =>x-41+41=-36+41 (add 41 to both sides to get only the unknown to the left of the equality sign) 0>x=5 Last step is to use the value of x=5 in the original equation to see if the left side equals the right side. I'll leave …
How do you simplify first and then solve −(1 + 7x) − 6(−7 − x)
2014年9月28日 · -( 1 + 7x) -6 (-7-x) = 36 it can be written as ; -1 ( 1 + 7x) -6 ( 7-x) =36 -1*1 + (-1) 7x -6*7 -6*(-x)= 36 -1 + -7x -42 + 6x =36 -1 -42 -7x +6x = 36 -43-x = 36 ...
How do you solve -( 2 + 7x ) - 6( - 7- x ) = 36? | Socratic
2016年9月23日 · x=4 Remove the brackets first. Be Careful with the negative signs -( 2 + 7x ) - 6( - 7- x ) = 36 -2-7x +42+6x = 36" "larr collect like terms and re-arrange, 40-36 = x" "larr move the variables to the RHS 4 = x
Plz help Solve for x? - Socratic
2018年1月19日 · x = 36/(4(3(dy/dx)+2)^2) + 7/4 I am assuming thaty you want to solve for x in terms of dy/dx rather than in terms of dy and dx. dy/dx=2/sqrt(4x-7)-2/3 Replace dy/dx by D to simplify notation until the end.
How do you solve log_6 x -log_6(x-6)=1? - Socratic
2017年1月9日 · x=7.2 Using the Rule : log_ma-log_mb=log_m(a/b), we get, log_6(x/(x-6))=1.....(1) Since, log_ma=n rArr m^n=a, we have, from (1), x/(x-6)=6^1=6 :. x=6(x-6)=6x-36 :. 5x=36 rArr x=36/5=7.2 This root satisfy the given eqn. Hence, x=7.2 is the Soln.
How do you solve x^2+8x+7=0? - Socratic
2015年8月15日 · Since (a - b + c = 0), use the shortcut. The 2 real roots are (- 1) and (-c/a = - 7). Reminder of Shortcut: a. When a + b + c = 0: 2 real roots: (1) and (c
Distributive Property for Multi-Step Equations - Algebra - Socratic
For example, the expression #5(x + 6)# can apply the distributive property to derive #5x + 30#. WHICH form makes it easier for you to obtain the final solution is up to you, not a math rule. In general, you may use the distributive function whenever there are elements of an expression that are distributed. Some good examples are here:
Integral by Partial Fractions - Calculus - Socratic
This integral can be solved by using the Partial Fractions approach, giving an answer of #2ln(x+5)-ln(x-2) + C#
If y varies directly as x^3 and y=36 when x=7, find y if x=4?
2018年5月1日 · If y varies directly as x^3 and y=36 when x=7, find y if x=4? (Round answer to the nearest hundredth) , find y if x=4 x = 4 .
What is the equation of the normal line of f(x)=sqrt(3x^2+2x
2015年11月10日 · y=-4/7x+36/7 f'(x)=frac{d}{dx}((3x^2+2x)^{1/2}) =1/2(3x^2+2x)^{-1/2}(6x+2) The tangent line should pass through the point (2, f(2)), and have a gradient of -1/{f'(2 ...